Projections of the impacts of COVID-19 on the Egyptian economy based on PIM modeling tools informed the Government of Egypt’s responses to the pandemic - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Egypt’s Ministry of Planning and Economic Development requested support from IFPRI to quantify the expected national and sectoral impacts of the pandemic on the Egyptian economy and investigate the consequences of various policy interventions in mitigating the disruptive effects of the virus. This collaboration was based on the use of PIM modeling tools. The results informed the Government’s responses to the pandemic.